The Evolution of Economic Research Strategies: The Role of the Concept of Strategizing V. L. Kvint - Alаbinа, T. A. (Upravlencheskoe konsulʹtirovanie, 2021)
The two-part series of articles reveals the purpose of the research as determining the place of the concept of strategizing of a Foreign Member of the Russian Academy of Sciences – Academician, Doctor of Economics, Professor V. L. Kvint in the system of economic research of strategies abroad, in the USSR and modern Russia on the basis of the description of the content and systematization of the basic concepts of strategizing and a review of foreign and domestic regional economic research, as well as the author’s identification of the key characteristics of this scientific school of strategy. The object of the research is the theory of strategies abroad, in the USSR and modern Russia. The subject of the research is the concept of V. L. Kvint’s strategizing in the system of economic research on strategy. The methodological tools include techniques and methods of system analysis, comparative analysis, logical analysis, principles of the dialectical-materialistic method of cognition and an integrated approach to the characterization of economic research, methods of generalization and concretization. The description of the study uses a historical approach and a temporary generalization based on the key milestones in the development of economic research on the theory of strategy and the methodology and practice of strategizing. As the results of present article, the main characteristics, systematization and content aspects of foreign and domestic economic research strategies are presented. The place of V. L. Kvint’s concept of strategizing in the system of economic research are determined. The article shows the practice of strategizing the research school.